Kunci Sukses Kepuasan Konsumen dalam Perkembangan Bisnis Perusahaan: Systematic Literature Review - Nofiyanti Nofiyanti; Masduki Asbari; Winanti Winanti; Andira Fajrin (Yayasan Aya Sophia Indonesia, 2024)
In the business world, apart from producing quality goods or services, the thing that needs to be maintained is consumer trust. Declining sales of goods or services can occur from consumer dissatisfaction with the goods or services offered by business people and this will have a big impact on the sustainability of the company's business. Apart from maintaining consumer satisfaction, it is necessary to carry out continuous innovation related to consumer satisfaction with the goods or services offered. One of the successes of a business actor or business owner is by having loyal consumers and one thing that can be used to assess consumer satisfaction is by conducting a survey containing the value of the services provided by the business actor or business owner. The impact of consumer satisfaction if the results obtained increase significantly in a positive direction, it will quickly grow in sales of goods or services being marketed. Consumer satisfaction can be obtained from several actions taken, namely by using a survey containing the factors that influence the satisfaction felt by consumers regarding service and convenience for consumers in the steps taken to use the goods or services offered by business actors. Due to the importance of the key to consumer satisfaction for business people, in this case the author conducted a literature review study using secondary data covering several types of businesses to find out what the keys to consumer satisfaction are. And the consumer satisfaction factor can influence a company's business development and is an important component in running a business.